1990
DOI: 10.1007/bf00308487
|View full text |Cite
|
Sign up to set email alerts
|

Transoral labiomandibular approach to basiocciput chordomas in childhood

Abstract: Many excellent reports have dealt with the various aspects of cranial chordoma. It remains a relatively rare neoplasm, particularly in younger children. The authors have had the opportunity to treat a 5-year-old child harboring a basiocciput chordoma. It extended from the mid-clivus to C3. A transoral labiomandibular approach was used, allowing its resection. No evidence of recurrence was noted 3 years later. A literature search confirmed the rarity of basiocciput chordoma in young children. The perioperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…10,22,28,[34][35][36]39,45 These include the transbasal, 13 extended frontal, 45 transseptal-transsphenoidal, 29-32 facial translocation, 26 transmaxillary, 25,38 midfacial degloving, 39,40 transoral, 9,12 mandible-splitting transoral, 29 transcervical-transclival, 50 and anterior cervical 8 approaches. 10,22,28,[34][35][36]39,45 These include the transbasal, 13 extended frontal, 45 transseptal-transsphenoidal, 29-32 facial translocation, 26 transmaxillary, 25,38 midfacial degloving, 39,40 transoral, 9,12 mandible-splitting transoral, 29 transcervical-transclival, 50 and anterior cervical 8 approaches.…”
Section: Choice Of Surgical Approach In Treating Clival Chordomasmentioning
confidence: 99%
See 1 more Smart Citation
“…10,22,28,[34][35][36]39,45 These include the transbasal, 13 extended frontal, 45 transseptal-transsphenoidal, 29-32 facial translocation, 26 transmaxillary, 25,38 midfacial degloving, 39,40 transoral, 9,12 mandible-splitting transoral, 29 transcervical-transclival, 50 and anterior cervical 8 approaches. 10,22,28,[34][35][36]39,45 These include the transbasal, 13 extended frontal, 45 transseptal-transsphenoidal, 29-32 facial translocation, 26 transmaxillary, 25,38 midfacial degloving, 39,40 transoral, 9,12 mandible-splitting transoral, 29 transcervical-transclival, 50 and anterior cervical 8 approaches.…”
Section: Choice Of Surgical Approach In Treating Clival Chordomasmentioning
confidence: 99%
“…

LTHOUGH it is generally agreed that surgery is the treatment of choice for clival chordomas, the question is still debated as to whether it is preferable to attempt a radical removal, which implies wide exposure, extensive dissection, and the potential for significant surgical morbidity, 17 or to determine the oncological features of the tumors and plan local control through more limited approaches. 2,7,17,19,36,38,[43][44][45][46][47]49 Nevertheless, experienced skull base surgeons have continued to advocate the valuable role of the transsphenoidal approach in the treatment of clival chordomas. 2,7,17,19,36,38,[43][44][45][46][47]49 Nevertheless, experienced skull base surgeons have continued to advocate the valuable role of the transsphenoidal approach in the treatment of clival chordomas.

…”
mentioning
confidence: 99%
“…This is especially significant because the edges of a midline pharyngotomy can rarely, if ever, be completely approximated. Nagib, et al, 11 reported a case of CSF leakage through a midline pharyngotomy that led to meningitis in a patient who had undergone resection of a clival chordoma. Although CSF leakage was not identified, Delagado, et al, 5 have reported the occurrence of meningitis in one of their three patients following resection; a midline pharyngotomy was used.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,[16][17][18][19][20] If the lesion extends more inferiorly from C2 to C4, additional inferior exposure can be gained with a median labiomandibular glossotomy or a mandibular swing-transcervical approach. 7,[21][22][23][24][25] This article focuses on the technical aspects of the transoral approach for accessing lesions of the ventral foramen magnum and craniovertebral junction. The transmaxillary, transpalatal, and transmandibular extensions are also reviewed.…”
mentioning
confidence: 99%